Depression status in relation to dental caries and salivary C-Reactive Protein among 17 years old secondary school female in Baghdad City/Iraq. - Noor A Al-Bazaz; Nada J MH Radhi (College of Dentistry/ University of Baghdad, 2021)
Background: Depression is a state of low mood and aversion to activity, it can affect a person's thoughts, behavior and sense of well-being. It can affect oral health and lead to an increased risk of dental caries. Dental caries is the most common oral infectious diseases that stresses the immune system and causes changes in cellular and molecular components of peripheral blood and C-Reactive Protein is one of these components, considered a key biomarker of inflammation. This study was conducted to assess the effect of depression status on dental caries among 17 years old secondary school female students in relation to salivary C-Reactive Protein. Materials and Methods: A cross sectional study was carried and the whole sample composed of 500 female students selected from First Alrasafa Directorate schools in Baghdad/ Iraq. Consent form was achieved from the ethical approval committee in College of Dentistry/University of Baghdad. All students were subjected to Children Depression Inventory questionnaire by Kovacs in 2011. Dental caries was registered according to Manji et al. 1989, Decay (1-4) Missing-Filled surface index. Subsamples were selected from high and low grade of depression to analyze C-Reactive Protein. Results: The percentage of occurrence of depression was 100%. The mean value of caries experience and severity were found to be higher among female students with high depression grade in comparison with low depression grade. The mean value for C-Reactive Protein was higher in high depression grade. There is a diversity in the results of caries experience with C-Reactive Protein. The percentage of depression occurrence was 100% which means a high degree of depression, and this could be due to the life difficulties, tension and economic issues that all lead to mental problems. The severity of dental caries increased as a result of stress and anxiety that may cause poor dental health. Psychological factors interact through complex pathophysiological and behavioral mechanisms that may cause elevated C-Reactive Protein. Conclusion: Depression has a negative impact on a person's oral health including dental caries. Elevated C-Reactive Protein levels have been associated with psychological depression.